ChemInform Abstract: Palladium‐Catalyzed Coupling of Benzoyl Halides with Aryltrifluorosilanes Leading to Diaryl Ketones. Issue 52 (6th December 2016) - Ogiwara, Yohei; Maegawa, Yuki; Sakino, Daisuke; Sakai, Norio
Abstract: The first Hiyama cross‐coupling of acyl halides or pseudohalides with aryltrifluorosilanes is described.